First Detection of Ligustrum necrotic ringspot virus, Cucumber mosaic virus, and Alternanthera mosaic virus in Mazus reptans in the United States - Henderson, D C (Plant disease, 2014)
Mazus reptans N.E. Br (creeping mazus; Phrymaceae) is a perennial flowering groundcover plant. A plant of M. reptans 'Alba' with mild mosaic symptoms was obtained from a Maryland nursery in 2010. Electron microscopy (EM) revealed slightly flexuous particles of 595 to 674 nm in length and smaller fragments, typical of carlaviruses. This sample was analyzed using a recently-developed Universal Plant Virus Microarray (UPVM [4]), and UPVM results confirmed by RT-PCR and sequencing. For UPVM analysis, complementary DNA (cDNA) was prepared from total nucleic acid extracts using a combination of oligo(dT) and random (6- to 9-mer) primers and high copy sequences (primarily ribosomal) were reduced using duplex-specific nuclease. Treated cDNA was labeled by incorporation of amino-allyl dUTP, followed by coupling of Cy3 dye and hybridization to a UPVM slide (4). Analysis of UPVM hybridization results using associated Uchip and T-Predict software (4) identified Ligustrum necrotic ringspot virus (LNRV; Carlavirus) and Cucumber mosaic virus subgroup I (CMV sgI; Cucumovirus). To confirm the UPVM results, we used NSNC-odT (3) primed cDNA, and LNRV-specific primer Lig1 (GTTGATCCTTTAGGTTTACAGGT) paired with NSNC-odT to amplify the 3' region of the LNRV genome. We used random-primed cDNA with generic cucumovirus coat protein (CP) primers CPTALL-5/CPTALL-3 (2), and CMV subgroup (sg)-specific primers CMV I(F)/CMV I(R) and CMV II(F)/CMV II(R) (1) to amplify the full CMV CP gene or internal portions. A ~1.35 kb PCR product from the LNRV-specific amplification was cloned, sequenced (GenBank Accession No. KJ187250), and found to have 84.6% nt identity to the LNRV-type (EU074853), with 97.0% CP amino acid (AA) identity and 94.7% nucleic acid binding protein (NABP) AA identity to LNRV-Impatiens (GQ411367) excluding an additional 14 N-terminal AA present in the NABP of both the type and impatiens isolates. CMV sgI-specific primers yielded a product of ~600 bp, and generic primers CPTALL-5/CPTALL-3 a ~940 bp product; no product was obtained with sgII-specific primers. The full CP gene product was cloned and sequenced (KJ486271), and had 99% nt identity to CMV-Fny (U20668), a subgroup I isolate, and <75% to characterized sgII isolates (5); CMV-Mazus CP had 100% AA identity to CMV-Fny, and <82.6% to the sgII isolates. One plant of purple M. reptans obtained in 2012, and four purple-flowered and three 'Alba' in 2014 from three separate sources, also showed mild mosaic. LNRV was detected by EM of carlavirus-like particles (2012 sample), and in all eight plants by LNRV-specific PCR and sequencing (KJ187247 for 2012 sample). Alternanthera mosaic virus (AltMV; Potexvirus) was also detected from two plants of 'Alba' by PCR, sequencing, bioassay (Nicotiana benthamiana, Chenopodium quinoa), and ELISA (3). To our knowledge, this is the first report of LNRV, CMV, or AltMV in M. reptans, a commonly grown groundcover plant. While CMV and AltMV are known to have wide host ranges, LNRV has previously been reported only from Ligustrum and Impatiens sp. The mild symptoms hinder symptom-based detection, and M. reptans may thus serve as a conduit for LNRV, CMV, and AltMV infection of other ornamentals. References: (1) S. Chen et al. Acta Biochim. Biophys. Sin. 43:465, 2011. (2) S. K. Choi et al. J. Virol. Meth. 83:67, 1999. (3) J. Hammond et al. Arch. Virol. 151:477, 2006. (4) J. Hammond et al. Phytopathology 102(S4):49, 2012. (5) J. Thompson and M. Tepfer. J. Gen. Virol. 90:2293, 2009